Dynamics of PO2 and VO2 in resting and contracting rat spinotrapezius muscle - Golub, Aleksander S.; Song, Bjorn K.; Nugent, William H.; Pittman, Roland N. (Frontiers in Physiology, 2023)
This study examined changes in interstitial PO2, which allowed calculation of V ̇O2 during periods of rest, muscle contraction and recovery using an in situ rat spinotrapezius muscle preparation. The PO2 was measured using a phosphorescence quenching technique microscopy and the muscle V ̇O2 was calculated as the rate of O2 disappearance during brief periods of muscle compression to stop blood flow with a supra-systolic pressure. The PO2 and V ̇O2 measurements were made during "5 s compression and 15 s recovery" (CR) cycles. With all three stimulation frequencies, 1, 2 and 4 Hz, the fall in interstitial PO2 and rise in V ̇O2 from resting values occurred within the first 20 s of contraction. The PO2 during contraction became lower as stimulation frequency increased from 1-4 Hz. V ̇O2 was higher at 2 Hz than at 1 Hz contraction. With cessation of stimulation, PO2 began increasing exponentially towards baseline values. After 1 and 2 Hz contraction, the fall in muscle V ̇O2 was delayed by one CR cycle and then exponentially decreased towards resting values. After 4 Hz stimulation, V ̇O2 increased for 2 cycles and then decreased. The post-contraction transients of PO2 and V ̇O2 were not synchronous and had different time constants. With further analysis two distinct functional responses were identified across all stimulation frequencies having PO2 during contraction above or below 30 mmHg. The corresponding V ̇O2 responses were different -for "high" PO2, muscle V ̇O2 reached high levels, while for the "low" PO2 data set muscle V ̇O2 remained low. Recovery patterns were similar to those described above. In summary, local microscopic PO2 and V ̇O2 were measured in resting and contracting muscle in situ and the post-contraction transients of PO2 and V ̇O2 were all much slower than the onset transients.